Practical Aviation Security : Predicting and Preventing Future Threats. - Price, Jeffrey (Elsevier Science, 2012)
The second edition of Practical Aviation Security is a complete guide to the aviation security system, from crucial historical events to the policies, policymakers, and major terrorist and criminal acts that have shaped the procedures in use today. The tip-of-the-spear technologies that are shaping the future are also addressed. This text equips readers in airport security or other aviation management roles with the knowledge to implement the effective security programs, to meet international guidelines, and to responsibly protect facilities or organizations of any size. Using case studies.